[Church on Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a church on Heimaey. The white church with a rectangular tower entrance and red roofs sits on a grey platform in a grass patch. The rest of the city sits behind a stone wall to the left and on top of a hill to the right. A dark statue of a hooded figure sits on a rock platform along the right edge of the photograph. A dark volcano, Eldfell, is visible in the background below a layer of white clouds.